Safety, reactogenicity, and immunogenicity of Ad26.COV2.S: Results of a phase 1, randomized, double-blind, placebo-controlled COVID-19 vaccine trial in Japan. Issue 9 (24th February 2023) - Tsuchiya, Yumi; Tamura, Hiroshi; Fujii, Koji; Numaguchi, Hirotaka; Toyoizumi, Kiichiro; Liu, Tina; Le Gars, Mathieu; Cárdenas, Vicky; Eto, Takashi
Highlights: Japanese adults aged 20–55 years or ≥ 65 years received Ad26.COV2.S or placebo. A homologous booster dose was given 2 months (56 days) after the first dose. Reactogenicity was increased with the higher dose (1 × 10 11 vp) in both age groups. Post-booster immunogenicity was higher in younger versus older adults. Neutralizing and binding antibody levels peaked at/around Day 71 in both age groups. Abstract: Background: This study evaluated safety, reactogenicity, and immunogenicity of a 2-month homologous booster regimen of Ad26.COV2.S in Japanese adults. Methods: In this multicenter, placebo-controlled, Phase 1 trial, adults (Cohort 1, aged 20–55 years, N = 125; Cohort 2, aged ≥ 65 years, N = 125) were randomized 2:2:1 to receive Ad26.COV2.S 5 × 10 10 viral particles (vp), Ad26.COV2.S 1 × 10 11 vp, or placebo, followed by a homologous booster 56 days later. Safety, reactogenicity, and immunogenicity were assessed. Results: Two hundred participants received Ad26.COV2.S and 50 received placebo. The most frequent solicited local adverse event (AE) was vaccination-site pain, and the most frequent solicited systemic AEs were fatigue, myalgia, and headache. After primary vaccination, neutralizing and binding antibody levels increased through Day 57 (post-prime) in both cohorts. Fourteen days after boosting (Day 71), neutralizing antibody geometric mean titers (GMTs) had almost reached their peak value in Cohort 1 (5 × 10 10 vp: GMT = 1049; 1 × 10 11 vp: GMT = 1470) and peaked in Cohort 2 (504; 651); at Day 85, GMTs had declined minimally in Cohort 2. For both cohorts, binding antibody levels peaked at Day 71 with minimal decline at Day 85. Conclusion: A single dose and homologous Ad26.COV2.S booster increased antibody responses with an acceptable safety profile in Japanese adults (ClinicalTrials.gov Identifier: NCT04509947).